The Type Ia supernovae rate with Subaru/XMM-Newton Deep Survey - Okumura, J; Ihara, Y; Doi, M; Morokuma, T; Pain, R; Totani, T; Barbary, K; Takanashi, N; Yasuda, N; Aldering, G; Dawson, K; Goldhaber, G; et al. (Astronomical Society of Japan, 2014)
We present measurements of the rates of high-redshift Type Ia supernovae derived from the Subaru/XMM-Newton Deep Survey (SXDS). We carried out repeated deep imaging observations with Suprime-Cam on the Subaru Telescope, and detected 1040 variable objects over 0.918deg2 in the Subaru/XMM-Newton Deep Field. From the imaging observations, light curves in the observed i ′ band are constructed for all objects, and we fit the observed light curves with template light curves. Out of the 1040 variable objects detected by the SXDS, 39 objects over the redshift range 0.2 < z < 1.4 are classified as Type Ia supernovae using the light curves. These are among the most distant SN Ia rate measurements to date. We find that the Type Ia supernova rates increase up to z ∼ 0.8 and may then flatten at higher redshift. The rates can be fitted by a simple power law, rV(z) = r0(1 + z)α with r0=0.20+0.52-0.16(stat.)+0.26-0.07(syst.) × 10 -4yr-1Mpc-3, and α =2.04 +1.84-1.96(stat.)+2.11-0.86(syst.). © 2014 The Author.